Cognitive behaviour therapy in chronic fatigue syndrome. Issue 2 (February 1991) - Butler, S; Chalder, T; Ron, M; Wessely, S
Abstract : Fifty patients fulfilling operational criteria for the chronic fatigue syndrome (CFS), and who had been ill for a mean of five years, were offered cognitive behaviour therapy in an open trial. Those fulfilling operational criteria for depressive illness were also offered tricyclic antidepressants. The rationale was that a distinction be drawn between factors that precipitate the illness and those that perpetuate it. Among the latter are cognitive factors such as the belief that physical symptoms always imply tissue damage, and behavioural factors such as persistent avoidance of activities associated with an increase in symptoms. Therapy led to substantial improvements in overall disability, fatigue, somatic and psychiatric symptoms. The principal problems encountered were a high refusal rate and difficulties in treating affective disorders. Outcome depended more on the strength of the initial attribution of symptoms to exclusively physical causes, and was not influenced by length of illness. These results suggest that current views on both treatment and prognosis in CFS are unnecessarily pessimistic. It is also suggested that advice currently offered to chronic patients, to avoid physical and mental activity, is counterproductive.